Brand and talent - Keohane, Kevin (London Kogan Page Limited, 2014)
"In Brand and Talent, Kevin Keohane makes the connection between how an organization's purpose, ambition, strategy and positioning should drive - and be driven by - its talent agenda. He looks at how organizations can better communicate with people before, during and after their association with the enterprise and presents a "joined up" approach that encompasses the needs of brand, marketing, human resources, corporate communications, internal communications and IT. He integrates academic and commercial evidence, as well as practical advice and includes case studies and interviews with thought leaders, such as Tom Crawford, current Head of Internal Comms and Engagement at O2 and UK Director of Internal Comms at British Gas; Gaurav Mishra, Asia Director of Social Media, MSLGROUP; Paloma Alos, Head of Global Marketing KPMG; Denmark intranet guru Brett Minchington and others. Many books talk about brand, still more about talent, yet leading organizations are realising their identity as a service/product provider is virtually inseparable from their identity as a place that attracts, motivates and benefits from thriving talent. In Brand and Talent, author Kevin Keohane looks at how organisations can better communicate with people before, during and after their association with the enterprise. He presents a "joined up" approach that encompasses the needs of brand, marketing, human resources, corporate communications, internal communications and IT. He integrates academic and commercial evidence, as well as practical advice and includes case studies and interviews"--Provided by publisher.
Includes bibliographical references (pages 208-214) and index.
Keywords: Branding (Marketing); Personnel management; Organizational effectiveness; Branding (Marketing) -- Case studies; Personnel management -- Case studies; Organizational effectiveness -- Case studies